'Beauty is more than beauty': Examining Karl Foerster's position in German garden culture. Issue 2 (4th May 2017) - Hopstock, Lars
Abstract: Karl Foerster (1874–1970) can arguably be called Germany's most influential modern horticulturist. However, despite general recognition of his work, very little rigorous scholarly writing has been devoted to him. This may be due to the lyricism of his writing and the ambiguous character of his ambitions that oscillate between anti-modernist neo-romanticism and progressive humanism. The following text primarily provides an introduction to his career and his significance for German garden culture. The mysticism in Foerster's writings, which is to a large extent responsible for his fame, will be dealt with briefly, before exposing the scope of his work and its impact on twentieth-century landscape architecture. While it is widely acknowledged that the modern German dwelling garden, which developed around 1930, owes much to Foerster's promotion of hardy perennials with a close-to-nature character, several research topics can be identified that are awaiting deeper investigation.